Nitrogen and Phosphorus Additions Alter the Abundance of Phosphorus-Solubilizing Bacteria and Phosphatase Activity in Grassland Soils - Widdig, Meike; Schleuss, Per-M.; Weig, Alfons R.; Guhr, Alexander; Biederman, Lori A.; Borer, Elizabeth T.; Crawley, Michael J.; Kirkman, Kevin P.; Seabloom, Eric W.; Wragg, Peter D.; Spohn, Marie (Frontiers in Environmental Science, 2019)
Microorganisms mobilize phosphorus (P) in soil by solubilizing bound inorganic P from soil minerals and by mineralizing organic P via phosphatase enzymes. Nitrogen (N) inputs are predicted to increase through human activities and shift plants to be more P limited, increasing the importance of P mobilization processes for plant nutrition. We studied how the relative abundance of P-solubilizing bacteria (PSB), PSB community composition, and phosphatase activity respond to N and P addition (+N, +P, +NP) in grassland soils spanning large biogeographic gradients. The studied soils are located in South Africa, USA, and UK and part of a globally coordinated nutrient addition experiment. We show that the abundance of PSB in the topsoil was reduced by 18 % in the N and by 41 % in the NP treatment compared to the control. In contrast, phosphatase activity was significantly higher in the N treatment than in the control across all soils. Soil C:P ratio, sand content, pH, and water-extractable P together explained 71 % of the variance of the abundance of PSB across all study sites and all treatments. Further, the community of PSB in the N and NP addition treatment differed significantly from the control. Taken together, this study shows that N addition reduced the relative abundance of PSB, altered the PSB community, and increased phosphatase activity, whereas P addition had no impact. Increasing atmospheric N deposition may therefore increase mineralization of organic P and decrease solubilization of bound inorganic P, possibly changing P mobilization processes in grassland soils. Consequently, in ecosystems in which plant P nutrition depends on bound inorganic P, increased N inputs might diminish P supply and thus aggravate P limitation and constrain plant productivity.